RESPONSE SURFACE METHODOLOGY APPLIED TO OXALIC ACID HYDROLYSIS OF OIL PALM EMPTY FRUIT BUNCH BIOMASS FOR D-XYLOSE PRODUCTION - SURYAD, HERMAN; YANUAR, ARRY; HARMITA; RACHMADANI, PUTRI WINNY (International Journal of Applied Pharmaceutics, 2020)
Objective: The study aimed to identify the best conditions using oxalic acid for hydrolysis of hemicellulose in oil palm empty fruit bunch (OPEFB) biomass. Methods: The analytical method of high-performance liquid chromatography (HPLC) was using a SUPELCOSIL LC-NH2 column, refractive index detection detector, and three compositions of the mobile phase. At first, the hydrolysis of hemicellulose in OPEFB powder was optimized by applying a response surface methodology. A three-variable, six-central composite design was used for the experiments. Temperature (between 95°C and 135°C), reaction time (between 10 and 110 min), and oxalic acid concentration (between 1% and 7% [w/v]) were evaluated by running 15 different experiments at constant biomass concentrations. Then, hydrolysis was optimized again at the constant temperature selected with three variables: OPEFB concentration, reaction time, and oxalic acid concentration. Hydrolysate samples were detoxified with carbon active, and furfural compound was analyzed by gas chromatography with flame ionization detector. Results: The optimum condition of HPLC was using acetonitrile: water (9:1) at a flow rate of 1.0 ml/min. The first hydrolysis results showed a high yield of D-xylose produced, which was 6.40 g D-xylose/100 g OPEFB biomass, with a xylose recovery of 93.8%. However, this result was not yet optimum. Further hydrolysis at constant temperature experiment produced the highest xylose yield of 13.13%, equivalent to 32 g/l D-xylose. Conclusion: The yield of D-xylose from mild hydrolysis using oxalic acid was similar to that using dilute sulfuric acid as used in the previous study by Rahman et al.